Pengaruh Nation Branding “Pesona Indonesia” Terhadap Preferensi Tujuan Wisata Masyarakat Kota Bandung - Steffi Priani Sugi; Astia Putri (Universitas Kristen Maranatha, 2019)
Tourism is one industry that has the potential to drive the economy and provide a positive impact on more developed national development. Nation Branding program carried out by the Ministry of Tourism and Creative Economy (Kemenparekraf) to improve the image and attract tourists to various destinations to Indonesians themselves. The research method used in this study is descriptive explanatory method using questionnaires and observations. The sampling method used is nonprobiliy sampling. in the study there are independent or independent variables (X) namely Nation Branding consisting of exports, governance, investment, culture, people, and tourism. The dependent variable (Y) is the preference of the tourist destination.The results showed that the nation branding variable had a significant influence on tourist destination preferences. The independent variable of the most influential nation branding is culture and tourism. The independent variable of the most influential nation branding is culture and tourism. The author recommends to increase the tagline